Financial burden in the form of medical and non-medical out-of-pocket expenses on the family of children admitted to a pediatric intensive care unit in India - Varun Ravindra Jagtap; Sushma Save; Praveen Unki (SpringerOpen, 2023)
Abstract Background Pediatric intensive care unit (PICU) admissions can have significant repercussions on families, including financial burdens and psychological distress. Not only do they face the overwhelming concern for their child's health and well-being, but they are also confronted with a range of practical and financial difficulties. Coping strategies play a vital role in mitigating the negative impact of PICU admissions on families. Various coping mechanisms, such as seeking social support, engaging in problem-solving, and utilizing emotional regulation techniques, can help families navigate the challenges they face. The objectives of the study are to understand the array of financial implications in the form of out-of-pocket expenses (OOPE) and to quantify with a better understanding of the composition of out-of-pocket expenses in the form of medical and non-medical expenses. It also aimed to determine the loss of productive hours in a family and to understand the burden of OOPE in relation to the income of the family. Methods This prospective observational study was conducted in the pediatric intensive care unit (PICU) of a tertiary care hospital over a period of 6 months after obtaining permission from the institutional ethics committee. Data pertaining to financial burden was collected with the help of Structured questionnaires which included the following categories travel, meals, accommodation, and incidental expenses were considered as non-medical expenses while all medicine costs and investigations were considered as medical expenses. The quantitative data were presented as the means ± SD as median with 25th and 75th percentiles (interquartile range) and were analyzed using ANOVA (for more than two groups) and independent t test (for two groups). Results More than half of the children (39(55.71%)) were not enrolled under any government scheme. The mean value of total medical and non-medical costs was 2525 ± 4035.28 and 2234.29 ± 846.84 Indian rupees. The mean value of total out-of-pocket expenses incurred per day (Indian rupees) on day 1, day 2, day 3, day 4, and day 5 were 1304 ± 587.2, 1208.86 ± 3773.84, 814.57 ± 565.03, 807.71 ± 522.76, and 699.86 ± 807.02 respectively. Conclusion Families of children admitted to the pediatric intensive care unit incurred catastrophic health expenditure with the cost of medicine contributing a major share. The lowest income brackets had much higher, more than twice the financial burden compared to the higher income group. Almost all families experienced a high loss of productivity in the form of a number of days lost due to the PICU admission of a child. Enrolment in government schemes helped to reduce OOPEs though better coverage of these schemes is needed.